Applying Anki to enhance vocabulary acquisition of first-year students at a university in Hanoi = Sử dụng Anki nhằm nâng cao việc học từ vựng của đối tượng sinh viên năm nhất tại một trường đại học ở Hà Nội - Nguyễn, Phương Trinh (2020)
First, concerning the effect of Anki on vocabulary learning, according to the analysis of the pre-test and post-test results, Anki can assist language learners to foster their vocabulary range. Therefore, it can be regarded as an effective vocabulary learning tool to some extent. Concerning the learners’ perceptions toward this digital flashcard program, generally, they came to appreciate it in terms of its usefulness and enjoyment; however, some learners were of the opinion that using it was not easy for beginners nor highly motivational. 12. Practical applicability, if any: According to the results of this study, Anki is reported to be useful and enjoyable when it comes to learning L2 vocabulary; hence, the usage of this web-based flashcards program is recommended for language learners. It is advisable to utilize it as either a mandatory practice source in the class or an optional source out of the classroom beside other learning methods. In addition, it is also useful for teachers who wish to incorporate a vocabulary learning program in their courses with the aim of helping their students memorize vocabulary better.